Catechin-Rich Gambir (Uncaria gambir Roxb.) as a Nutraceutical Agent: Modulation of IL-10 Gene Expression and Cognitive Function in Elderly - Yusuf, Rahmi Novita; Arman, Eliza; Anggresani, Lia (Universitas Andalas, 2026)
Aging is associated with increased oxidative stress and chronic inflammation, which contribute to cognitive decline. Modulation of anti-inflammatory pathways, particularly through interleukin-10 (IL-10), may offer a neuroprotective strategy. Catechins, polyphenolic compounds with antioxidant and anti-inflammatory properties, are abundant in Uncaria gambir Roxb., an Indonesian plant with high catechin content. This study aimed to evaluate the effects of catechin-rich gambir supplementation on cognitive function and IL-10 gene expression in older adults. A randomized, double-blind, placebo-controlled trial was conducted involving 58 participants aged ≥60 years with mild cognitive impairment (MoCA-Ina scores 20–25). Participants received either 224 mg/day of catechin or placebo for 12 weeks. Cognitive function was assessed using the MoCA-Ina, and IL-10 gene expression was measured using quantitative real-time PCR (qRT-PCR). Catechin supplementation significantly improved cognitive function compared to placebo (p < 0.001) and increased IL-10 gene expression after 12 weeks (p < 0.001). These findings suggest that gambir-derived catechins may contribute to cognitive improvement through modulation of anti-inflammatory pathways. However, further studies are required to confirm long-term effects and clinical applicability.